Discovering AutoCAD 2009 - Dix, Mark
Discovering AutoCAD 2009 offers a hands-on, activity-based approach to the use of AutoCAD as a drafting tool complete with techniques, tips, shortcuts, and insights that improve efficiency. Topics and tasks are carefully grouped to lead students logically through the AutoCAD command set, with the level of difficulty increasing steadily as skills are acquired through experience and practice. Straightforward explanations focus on what is relevant to actual drawing procedures, and illustrations show exactly what to expect on the computer screen. This edition features Web-based exercises, projects and new test questions for each chapter